Subtle Right Ventricular Affection in Patients with Acute Myocardial Infarction, Echocardiographic Assessment - Mohamed, Abdallah; Alramlawy, Shaaban; El-Hadidy, Samir; Affify, Mohamed Ibrahiem; Radwan, Waheed (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The right ventricle (RV) has historically received less attention than its counterpart of the left side of the heart, yet there is a substantial body of evidence showing that RV size and function are perhaps equally important in predicting adverse outcomes in cardiovascular diseases. AIM: The aim of our work was to evaluate incidence and impact of right ventricular (RV) affection in patients with acute left ventricular myocardial infarction subjected to primary percutaneous coronary intervention (1ry PCI). METHODS: The study was conducted on 80 patients who had acute left ventricle ST elevated myocardial infarction (LV STEMI) and subjected to 1ry PCI. The study was done in Cairo University, critical care department. All patients were studied within 2 days after 1ry PCI, RV function was assessed by echocardiography through tricuspid annular plane systolic excursion (TAPSE) and speckle tracking echocardiography. We excluded patients with RV infarction, moderate to severe tricuspid regurgitation, pulmonary hypertension, dilated cardiomyopathy, atrial or ventricular septal defect, and patients who had cardiac dysrhythmias. RESULTS: Out of 80 patients (64 men and 16 women) included in the study, 38 patients (47.5%) had TAPSE <1.7 cm, and 48 patients (60%) had RV longitudinal strain less negative than −19%.There was a statistically significant relationship between RV affection and anterior STEMI, left anterior descending artery as an infarct-related artery, duration of intensive care unit stay, impairment of LV global and regional systolic function, in-hospital complications, and 1-year mortality. CONCLUSION: RV dysfunction is not uncommon in acute LV STEMI when using the definition of TAPSE <17 cm and RV longitudinal strain less negative than −19%.There was a significant relationship between RV dysfunction and poor outcome in patients with acute LV STEMI.